A technologically guided explanation of regulatory change in defence equipment markets - De Angelis, Alessandra (2020)
The thesis seeks to explain the emergence of a EU-rule based regime for European Defence Equipment Markets (EDEM). This development seems at first sight paradoxical because the armaments policy area has historically remained under the direct control of Member States and outside the competence of the EU institutions and policy-making processes. Going beyond existing academic explanations in the legal and political science literature, the present doctoral investigation has provided for a theoretically structured account of the role that technology and innovation dynamics have played in shaping the evolution of the industrial organisation, and, as a direct consequence of that, in determining patterns of institutional change in the regulatory constructs deputed to discipline military markets. More specifically, the argument being advanced is that technological change and innovation dynamics play a crucial role in explaining regulatory change in EDEM via the intermediate step of the transformation of military markets and their productive structures. A technologically guided explanation, deriving from extensive empirical investigation, has supported the elaboration of a multi-disciplinary theoretical framework, which has connected for the first time a body of evolutionary economics with EU public policy making literature. Such empirically supported theoretical account has introduced a brand new scholarly contribution to the subject of defence industries and equipment markets in Europe.